A Practical Approach to Spine Magnetic Resonance Imaging. Issue 3 (March 2020) - Shepard, Nicholas; Samim, Mohammad; Kim, Yong; Razi, Afshin
Abstract : Magnetic resonance imaging (MRI) plays an important role in the evaluation of patients with spine disorders, providing excellent evaluation of both normal and pathologic anatomy. Interpreting MRI findings can be difficult as anatomic abnormalities may not correlate with clinical symptoms and MRI may show abnormal findings in asymptomatic individuals. Using a systematic approach to interpreting a spinal MRI can help to achieve an accurate diagnosis and guide therapeutic decision-making, surgical intervention, and treatment monitoring.